2014
DOI: 10.1088/0004-637x/793/1/58
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Morphology of Large-Scale Structure: Evolution From Potential to Rotational Flow

Abstract: As an alternative way to describe the cosmological velocity field, we discuss the evolution of rotational invariants constructed from the velocity gradient tensor. Compared with the traditional divergence-vorticity decomposition, these invariants, defined as coefficients of the characteristic equation of the velocity gradient tensor, enable a complete classification of all possible flow patterns in the dark-matter comoving frame, including both potential and vortical flows. We show that this tool, first introd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…After defining the rotational invariants of tensor A ij , which essentially combines both potential and rotational information of A ij , Wang et al (2014) demonstrated that the distinct correlation between vorticity generation and cosmic web structure could be phenomenologically explained by a stochastic process that drives the transition from potential to rotational flow in their parameter space. To some extent, this generalized dynamics has a similar underlying philosophy to the approach of the effective field theory (EFT) of the large-scale structure (Baumann et al 2012;Carrasco et al 2012;Pajer & Zaldarriaga 2013;Hertzberg 2014;Mercolli & Pajer 2014), where new operators that are compatible with the symmetries of the problem were introduced to effectively describe the evolution of large-scale modes.…”
Section: Stochasticity and Effective Fluid Elementsmentioning
confidence: 99%
“…After defining the rotational invariants of tensor A ij , which essentially combines both potential and rotational information of A ij , Wang et al (2014) demonstrated that the distinct correlation between vorticity generation and cosmic web structure could be phenomenologically explained by a stochastic process that drives the transition from potential to rotational flow in their parameter space. To some extent, this generalized dynamics has a similar underlying philosophy to the approach of the effective field theory (EFT) of the large-scale structure (Baumann et al 2012;Carrasco et al 2012;Pajer & Zaldarriaga 2013;Hertzberg 2014;Mercolli & Pajer 2014), where new operators that are compatible with the symmetries of the problem were introduced to effectively describe the evolution of large-scale modes.…”
Section: Stochasticity and Effective Fluid Elementsmentioning
confidence: 99%
“…Therefore, as time progresses, vorticity is produced on ever larger scales. It is difficult to study analytically the production of vorticity and many works have used dedicated N -body simulations in order to obtain its magnitude and time/scale dependence [18,19,20]. In particular, the results of [19,20] show how vorticity is correlated with the density contrast and that it becomes important (as compared to the velocity divergence) at small scales and/or at early times.…”
Section: Discussionmentioning
confidence: 99%
“…For ν = 0 the system of equations (18)(19)(20)(21)(22)(23) reduces to the standard case of an uncoupled quintessence field with exponential potential. In particular, if λ 2 < 3 there is a stable (accelerated for λ 2 < 2) attractor with Ω φ = 1 and w φ = w eff = −1 + λ 2 3 (scalar field-dominated solution); and, if λ 2 > 3, a stable attractor with Ω φ = 3 λ 2 and w φ = w eff = 0 (scaling solution).…”
Section: Limiting Casesmentioning
confidence: 99%
“…1. Illustration of structure type classification in Lagrangian invariants space, according to the lich procedure (see also figure 3 in Wang et al ., 2014). We show the s3 − s2 plane for s1 < 0 (left panel) and s1 > 0 (right panel).…”
Section: Lichmentioning
confidence: 99%